Pengaruh Pemberian Beasiswa Pendidikan Terhadap Partisipasi Berorganisasi Mahasiswa STKIP PGRI Tulungagung - Fajar Hendro Utomo; Agus Timan; Muhamad Ahmad Yusuf Sobri (Kelola: Jurnal Manajemen Pendidikan, 2020)
The development of student organizations' participation through student participation in student organizations has not received serious attention, despite the fact that the existence of student organizations on the campus of STKIP PGRI Tulungagung . Not optimal participation of students who are members of the student organization, the method used in this research is quantitative analysis with data analysis techniques filling questionnaires by scholarship recipients. Descriptive method has to do with the exposure of a phenomenon or the relationship between two or more phenomena, from the results of data collection and The above analysis needs to be developed a policy regarding the granting of scholarships to students who are not only smart, need financial assistance, but also students who are capable of emotional and empathic to both the environment and the institution or not only IQ but also EQ